A synergistic modification method for removing heavy metals from fly ash, modified fly ash and application

CN122913185APending Publication Date: 2026-10-16HUANENG LUOYUAN POWER GENERATION CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611260949.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

物理分选法包括分级、磁选和重选,物理分选法操作简单、无二次污染,但对赋存于玻璃体晶格中的重金属脱除效率有限

Benefits of technology

(1)建材掺合料领域:比表面积增大和玻璃体结构破坏使粉煤灰的火山灰活性显著提升,可加速水泥水化反应,提高混凝土的早期强度和后期强度增长;同时,表面活性的增强改善了粉煤灰与水泥基材料的界面结合力,有助于提升混凝土的致密性和耐久性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122913185A_ABST
    Figure CN122913185A_ABST
Patent Text Reader

Abstract

The application discloses a kind of synergic modification method for removing heavy metal in fly ash and modified fly ash and application, belong to solid waste harmless treatment and resource utilization technical field.The method of the present application is that the original fly ash is subjected to magnetic separation, and the magnetic component is removed to obtain non-magnetic fly ash;The non-magnetic fly ash is mixed with an organic complexing agent solution with a mass concentration of 0.05% to 0.5%, and is subjected to ultrasonic treatment at a temperature of 40°C to 80°C.During the ultrasonic treatment, the heavy metal is released and captured by the organic complexing agent to obtain modified fly ash.The present application combines magnetic separation, ultrasonic treatment and the synergistic effect of the organic complexing agent, which can achieve high removal rate of heavy metal in fly ash and reduce the amount of organic complexing agent used.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid waste harmless treatment and resource utilization technology, specifically involving a synergistic modification method for removing heavy metals from fly ash, modified fly ash, and its application. Background Technology

[0002] Fly ash is a major solid waste generated by coal-fired power plants, with huge annual emissions. Its main components are oxides such as SiO2, Al2O3, FeO / Fe2O3, CaO, and TiO2, and it is classified into high-calcium ash and low-calcium ash based on calcium content. Its particles are mostly glassy, ​​with a porosity of 50%–80%. The chemical composition of fly ash is similar to that of clay, and it is mainly used to produce fly ash cement, fly ash bricks, fly ash silicate blocks, fly ash aerated concrete, and other building materials. It can also be used as agricultural fertilizer and soil conditioner, recycled industrial raw materials, and as an environmental material. However, fly ash itself is usually enriched with heavy metals such as lead, cadmium, chromium, and arsenic. Direct use in building materials or soil improvement poses an environmental leaching risk, limiting the safety of its resource utilization.

[0003] Existing methods for removing heavy metals from fly ash mainly include physical sorting and chemical elution. Physical sorting methods include grading, magnetic separation, and gravity separation. These methods are simple to operate and produce no secondary pollution, but their removal efficiency for heavy metals located in the glassy crystal lattice is limited. Chemical elution methods, such as acid leaching and complexation, while achieving high removal rates for heavy metals, require large quantities of chemicals, are costly, and generate acidic wastewater that is difficult to treat.

[0004] Application No. 202310155112.3 discloses a method for preparing modified fly ash, its products and applications. It uses only a combination of pure physical sorting and ultrasound, which avoids chemical agents, but there is still room for improvement in the removal effect of some strongly bound heavy metals.

[0005] Therefore, it is necessary to develop a method for the synergistic removal of heavy metals from fly ash with low reagent dosage and high removal rate. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention provides a synergistic modification method for removing heavy metals from fly ash. This invention combines magnetic separation, ultrasound, and the synergistic effect of organic complexing agents, resulting in a high removal rate of heavy metals from fly ash and a low amount of organic complexing agent required.

[0007] To achieve the above objectives, the present invention employs the following technical solution: A synergistic modification method for removing heavy metals from fly ash includes the following steps: The raw fly ash is separated by magnetic separation to remove magnetic components, resulting in non-magnetic fly ash.

[0008] Non-magnetic fly ash is mixed with an organic complexing agent solution with a mass concentration of 0.05% to 0.5%, and then subjected to ultrasonic treatment at 40℃ to 80℃. During the ultrasonic treatment, heavy metals are released and captured by the organic complexing agent, resulting in modified fly ash.

[0009] When processing raw fly ash, the present invention first employs magnetic separation to remove magnetic components, taking into account the following factors: First, high-density magnetic minerals (such as magnetite) excessively reflect and scatter ultrasonic energy, weakening the cavitation effect. Removing magnetic components can ensure that the cavitation effect is concentrated on the surface of non-magnetic glass particles, thereby improving the effective efficiency of ultrasound.

[0010] Secondly, magnetic minerals often contain heavy metals in the form of fine inclusions. These structures are dense and difficult to break down by ultrasound. Removing them in advance can eliminate the physical shielding of these heavy metals.

[0011] Third, magnetic minerals have strong charges on their surfaces and contain variable-valence iron ions, which pose a risk of secondary adsorption of heavy metal cations released by ultrasound. Therefore, after magnetic separation, the non-magnetic components, mainly composed of aluminosilicate glass, have low surface activity, which is conducive to the stable existence of released heavy metal ions in the liquid phase and their full capture by organic complexing agents, thereby improving the overall removal efficiency.

[0012] After magnetic separation, an organic complexing agent is added to the non-magnetic fly ash. With the assistance of ultrasound, the non-magnetic fly ash undergoes ultrasonic cavitation, which destroys the glassy coating on the surface of the fly ash particles, promoting the release of internal heavy metals. At the same time, the low-concentration organic complexing agent captures heavy metal ions in a timely manner, achieving efficient removal of heavy metals such as lead and cadmium.

[0013] In a preferred embodiment of the present invention, the ratio of non-magnetic fly ash to organic complexing agent solution is 1g:3mL to 8mL.

[0014] In a preferred embodiment of the present invention, the mass concentration of the organic complexing agent is 0.1%, and the ratio of non-magnetic fly ash to organic complexing agent solution is 1g:5mL.

[0015] In a preferred embodiment of the present invention, the ultrasonic frequency is 40kHz to 80kHz and the ultrasonic time is 10min to 40min during ultrasonic treatment.

[0016] In a preferred embodiment of the present invention, the ultrasonic temperature is 60°C, the ultrasonic frequency is 60kHz, and the ultrasonic time is 30min.

[0017] In a preferred embodiment of the present invention, the magnetic separation method is as follows: magnetic separation for 5 min to 45 min at a magnetic separation intensity of 800 kA / m to 1200 kA / m.

[0018] In a preferred embodiment of the present invention, the magnetic separation method is as follows: magnetic separation for 5 minutes at a magnetic separation intensity of 1000 kA / m.

[0019] Processing according to the above parameter ranges can effectively remove heavy metal ions from fly ash.

[0020] In a preferred embodiment of the present invention, the organic complexing agent is one or more selected from citric acid, oxalic acid, tartaric acid, or ethylenediaminetetraacetic acid. More preferably, the organic complexing agent is citric acid, because citric acid has the highest removal rate for heavy metals and is biodegradable.

[0021] The present invention also includes a post-processing step after the ultrasonic treatment. Specifically, the ultrasonic product is subjected to solid-liquid separation to obtain a solid product, and the solid product is dried to obtain modified fly ash.

[0022] During the drying process, the drying temperature is 105℃~110℃ and the time is 2h~6h.

[0023] This invention also provides modified fly ash prepared by the above-mentioned synergistic modification method. Compared with the original fly ash, the modified fly ash prepared by this invention has the following significant structural advantages in terms of microstructure and surface chemical properties: (a) Physical structure: The original fly ash particles have a smooth, spherical glassy structure with a dense surface and closed pores, making it difficult for active oxides to contact the external environment. Ultrasonic cavitation is used to generate mechanical impact and micro-jets on the surface of the fly ash particles, causing micro-cracks in the dense glassy coating and leading to its gradual peeling off layer by layer. The resulting fly ash has the following characteristics: (1) Significantly increased specific surface area: The surface of fly ash particles changes from smooth and dense to rough and porous, and the specific surface area can be increased by more than 20% compared with the original ash, providing more reaction interfaces and adsorption sites for subsequent applications.

[0024] (2) Reduced glass content: The destruction of the glass coating exposes the originally protected internal active components such as SiO2 and Al2O3, effectively stimulating the pozzolanic activity of fly ash, which is beneficial to its hydration reaction in the building material cementing system.

[0025] (3) Improved particle size distribution: Ultrasonic cavitation causes some particles to deagglomerate and become finer, resulting in more uniform particle size and improved dispersion of fly ash in composite materials.

[0026] (II) The original fly ash surface is covered with a dense glassy shell, and the active SiO2 and Al2O3 are encapsulated by the Si-O-Al tetrahedral network, making it difficult for them to participate in chemical reactions. The ultrasonic cavitation of this invention breaks the Si-O-Si, Al-O-Al, and Al-O-Si covalent bonds, reducing the degree of polymerization of the glassy network and generating a large number of unsaturated broken bonds, specifically manifested as follows: (1) More active functional groups such as Si-OH and Al-OH are exposed on the surface of fly ash, which is conducive to the reaction with cement hydration product Ca(OH)2 to generate cementitious substances such as CSH gel.

[0027] (2) The surface zeta potential changes, and the adsorption affinity for both heavy metal cation and anion pollutants is enhanced.

[0028] (3) After treatment with organic complexing agents (such as citric acid or oxalic acid), some carboxyl groups (-COOH) can be embedded or grafted onto the surface of fly ash particles, giving the modified fly ash certain surface organic functionalization properties, and further improving its interfacial compatibility in composite materials.

[0029] The present invention also provides the application of the above-mentioned modified fly ash in the preparation of building material admixtures, saline-alkali land improvement materials or mine filling materials.

[0030] After being processed according to the preparation method of the present invention, the modified fly ash exhibits improved physicochemical properties compared to the original fly ash, and has the following advantages in application: (1) Building material admixture field: The increase in specific surface area and the destruction of glass structure significantly enhance the pozzolanic activity of fly ash, which can accelerate the cement hydration reaction and improve the early strength and later strength growth of concrete; at the same time, the enhanced surface activity improves the interfacial bonding force between fly ash and cement-based materials, which helps to improve the density and durability of concrete.

[0031] (2) Saline-alkali land improvement: The rough and porous particle surface and the increased specific surface area help to improve the adsorption and fixation capacity of fly ash for heavy metal ions in the soil; at the same time, the active functional groups exposed on the modified surface can undergo ion exchange or complexation with salt ions in the soil, which helps to reduce soil salinity.

[0032] In summary, this invention, through the synergistic effect of ultrasonic cavitation physical shell breaking and organic complexing agent chemical erosion, simultaneously removes heavy metals and revitalizes the structure of fly ash: transforming it from a smooth, dense, inert glassy substance into a rough, porous, functional material rich in active groups. This structural advantage not only ensures the product's environmental safety (meeting heavy metal leaching standards) but also endows the modified fly ash with higher resource utilization value in building materials, environmental protection, and other fields, achieving a balance between harmlessness and high value.

[0033] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention provides a synergistic modification method for removing heavy metals from fly ash. First, magnetic components are removed using magnetic separation to obtain non-magnetic fly ash. Then, for the non-magnetic fly ash, ultrasound and an organic complexing agent are used synergistically. Ultrasonic cavitation breaks the glassy coating of the fly ash, releasing heavy metal ions into the solution. The organic complexing agent promptly captures these heavy metal ions, effectively removing lead (Pb), cadmium (Cd), and chromium (Cr). Furthermore, this invention uses a low amount of organic complexing agent, with a concentration only 1 / 10 to 1 / 5 that of traditional chemical elution methods, resulting in less residual reagent in the wastewater and lower treatment costs. According to the modification method of this invention, the removal rate of cadmium (Cd) can reach up to 66.67%, lead (Pb) up to 45.79%, and chromium (Cr) up to 35.96%.

[0034] 2. When processing according to the modification method of the present invention, the organic complexing agent can be a biodegradable organic acid, such as citric acid or oxalic acid, and the washing wastewater can be discharged after simple neutralization.

[0035] 3. The modified fly ash treated by this invention can meet the requirements of relevant national environmental protection standards (such as GB 5085.3-2007) for heavy metal leaching concentration. The product has better safety and can be directly used in resource utilization pathways such as building material admixtures and soil improvement without further treatment. Attached Figure Description

[0036] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0037] Figure 1 This is a flowchart of the present invention. Detailed Implementation

[0038] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0039] When fly ash particles are burned at high temperatures, they form a large number of spherical glassy particles. Heavy metals such as Cd, Cr and Pb are encapsulated in the glassy particles as discrete tiny particles or iron oxides, resulting in low removal efficiency of these heavy metals.

[0040] Based on this, the present invention proposes a synergistic modification method for removing heavy metals from fly ash, the flowchart of which is shown below. Figure 1 As shown, when processing fly ash, magnetic separation is first performed to remove the magnetic components of the fly ash, thus avoiding the influence of the magnetic components on the subsequent ultrasonic steps. The non-magnetic fly ash obtained after magnetic separation is completed.

[0041] For the obtained non-magnetic fly ash, a synergistic treatment method of organic complexing agent and ultrasound is used. Ultrasound action destroys the glassy structure of fly ash particles, causing heavy metals to be released. Then, the organic complexing agent in the system directly binds with heavy metal ions. After ultrasound, the fly ash is obtained by filtration, washing and drying, thus achieving the removal of heavy metal ions from fly ash.

[0042] Only when ultrasound and organic complexing agents are present simultaneously can the heavy metals released by ultrasound be instantly captured by the organic complexing agent, with the release rate approximately equal to the capture rate. This avoids secondary adsorption and co-precipitation, achieving highly efficient removal. The functions of ultrasound and organic complexing agents are not interchangeable or substituted; they complement each other in terms of target, timing, and mode of action, forming the technical basis for a synergistic effect.

[0043] Taking citric acid (H3Cit) as an example, it undergoes stepwise dissociation in aqueous solution, reacting with heavy metal ions Pb. 2+ Cd 2+ Cr 3+ A cyclic chelate is formed, and the specific reaction formula is shown below:

[0044] The raw fly ash used in this invention was obtained from an appropriate amount of raw fly ash from a coal-fired power plant. The heavy metal content of the raw fly ash is shown in Table 1.

[0045] Table 1 Heavy metal content of raw fly ash

[0046] Example 1 This embodiment provides a synergistic modification method for removing heavy metals from fly ash, and the specific preparation method is as follows: Step 1: Perform magnetic separation on the raw fly ash under a magnetic field strength of 1000kA / m for 5 minutes to collect non-magnetic fly ash.

[0047] The non-magnetic fly ash was mixed with a 0.1% citric acid solution at a solid-liquid ratio of 1 g: 5 ml, placed in an ultrasonic reactor, and ultrasonically treated in a 60°C water bath for 30 min at an ultrasonic frequency of approximately 60 kHz. Immediately after ultrasonication, vacuum filtration was performed, and the filter cake was washed three times with deionized water until the pH of the washing solution was approximately 7. The washed solid was then dried in a 105°C forced-air drying oven for 4 h to constant weight, yielding the modified fly ash.

[0048] Example 2 This embodiment provides a synergistic modification method for removing heavy metals from fly ash, and the specific preparation method is as follows: Step 1: Perform magnetic separation on the raw fly ash under a magnetic field strength of 1000kA / m for 5 minutes to collect non-magnetic fly ash.

[0049] The non-magnetic fly ash was mixed with a 0.1% citric acid solution at a solid-liquid ratio of 1 g: 5 ml, placed in an ultrasonic reactor, and ultrasonically treated in a 60°C water bath for 20 min at a frequency of 60 kHz. Immediately after ultrasonication, vacuum filtration was performed, and the filter cake was washed three times with deionized water until the pH of the washing solution was approximately 7. The washed solid was then dried in a 105°C forced-air drying oven for 4 h to constant weight, yielding the modified fly ash.

[0050] Example 3 This embodiment provides a synergistic modification method for removing heavy metals from fly ash, and the specific preparation method is as follows: Step 1: Magnetic separation of raw fly ash is carried out under a magnetic field strength of 800 kA / m for 45 min to collect non-magnetic fly ash.

[0051] The non-magnetic fly ash was mixed with a 0.05% citric acid solution at a solid-liquid ratio of 1 g: 8 ml, placed in an ultrasonic reactor, and ultrasonically treated in a 40°C water bath for 10 min at an ultrasonic frequency of approximately 80 kHz. Immediately after ultrasonication, vacuum filtration was performed, and the filter cake was washed three times with deionized water until the pH of the washing solution was approximately 7. The washed solid was then dried in a 105°C forced-air drying oven for 4 h to constant weight, yielding the modified fly ash.

[0052] Example 4 This embodiment provides a synergistic modification method for removing heavy metals from fly ash, and the specific preparation method is as follows: Step 1: Magnetic separation is performed on the raw fly ash under a magnetic field strength of 1200kA / m for 4 minutes to collect non-magnetic fly ash.

[0053] The non-magnetic fly ash was mixed with a 0.5% ethylenediaminetetraacetic acid solution at a solid-liquid ratio of 1 g: 3 ml, and placed in an ultrasonic reactor. The mixture was ultrasonically treated in an 80°C water bath for 40 min at a frequency of 40 kHz. Immediately after ultrasonication, the mixture was vacuum filtered, and the filter cake was washed three times with deionized water until the pH of the washing solution was approximately 7. The washed solid was then dried in a 105°C forced-air drying oven for 4 h to constant weight, yielding the modified fly ash.

[0054] Example 5 This embodiment provides a synergistic modification method for removing heavy metals from fly ash, and the specific preparation method is as follows: Step 1: Perform magnetic separation on the raw fly ash under a magnetic field strength of 900 kA / m for 20 minutes to collect non-magnetic fly ash.

[0055] The non-magnetic fly ash was mixed with a 0.2% tartaric acid solution at a solid-liquid ratio of 1 g: 3 ml, and placed in an ultrasonic reactor. The mixture was ultrasonically treated in a 60°C water bath for 30 min at a frequency of 60 kHz. Immediately after ultrasonication, the mixture was vacuum filtered, and the filter cake was washed three times with deionized water until the pH of the washing solution was approximately 7. The washed solid was then dried in a 105°C forced-air drying oven for 4 h to constant weight, yielding the modified fly ash.

[0056] Comparative Example 1 This comparative example provides a synergistic modification method for removing heavy metals from fly ash, which is basically the same as Example 1, except that ultrasonic treatment is not performed; only 0.1 wt% citric acid is used and stirred at approximately 60°C for about 30 minutes. The specific preparation method is as follows: Step 1: Perform magnetic separation on the raw fly ash under a magnetic field strength of 1000kA / m for 5 minutes to collect non-magnetic fly ash.

[0057] The non-magnetic fly ash was mixed with a 0.1% citric acid solution at a solid-liquid ratio of 1 g: 5 ml and heated in a 60°C water bath for 30 min. Immediately after heating, vacuum filtration was performed, and the filter cake was washed three times with deionized water until the pH of the washing solution was approximately 7. The washed solid was then dried in a 105°C forced-air drying oven for 4 h to constant weight, yielding the modified fly ash.

[0058] Comparative Example 2 This comparative example provides a synergistic modification method for removing heavy metals from fly ash, which is basically the same as Example 1, except that the ultrasonic medium is pure water and citric acid is not added. The specific preparation method is as follows: Step 1: Perform magnetic separation on the raw fly ash under a magnetic field strength of 1000kA / m for 5 minutes to collect non-magnetic fly ash.

[0059] The non-magnetic fly ash was mixed with water at a solid-liquid ratio of 1 g: 5 ml and placed in an ultrasonic reactor. The mixture was ultrasonically treated in a 60°C water bath for 30 min at a frequency of approximately 60 kHz. Immediately after ultrasonication, the mixture was vacuum filtered, and the filter cake was washed three times with deionized water until the pH of the washing solution was approximately 7. The washed solid was then dried in a 105°C forced-air drying oven for 4 h to constant weight, yielding the modified fly ash.

[0060] The heavy metal content of the raw fly ash, Examples 1-2, and Comparative Examples 1-2 is compared below, as shown in Tables 2-4. The TCLP leaching results of the raw fly ash show that the leaching concentrations of some heavy metals are close to or exceed the relevant national standard limits, posing an environmental risk if used directly.

[0061] Table 2. Cadmium (Cd) content in fly ash before and after modification

[0062] Table 3. Lead (Pb) content in fly ash before and after modification

[0063] Table 4. Chromium (Cr) content in fly ash before and after modification

[0064] As shown in Tables 2-4, the modified fly ash obtained in Example 1 showed a significant reduction in the content of typical heavy metals such as lead and cadmium compared to the original fly ash, with a Pb removal rate exceeding 80% (the specific value may vary slightly depending on the composition of the original ash and the treatment conditions). TCLP leaching test results showed a Pb leaching concentration of 2.3 mg / L, lower than the limit of 5 mg / L in GB 5085.3-2007. This indicates that the synergistic effect of ultrasound and organic complexing agents is irreplaceable. This is because the physical breaking effect of ultrasonic cavitation releases heavy metals bound by the glass lattice, solving the problem of heavy metal release from fly ash. Then, the immediate trapping effect of the organic complexing agent stabilizes the released heavy metal ions in the liquid phase, solving the problem of heavy metal treatment. In other words, ultrasound and organic complexing agents are synchronized in time and co-located in space, forming an irreplaceable synergistic mechanism of immediate release and immediate trapping. In Example 2, after changing the type of organic complexing agent and the ultrasonic time, the content of typical heavy metals in the modified fly ash was also significantly reduced, with the effect being comparable to or slightly different from that in Example 1, indicating that the present invention has good adaptability to different organic complexing agents.

[0065] In Comparative Example 1, no ultrasonic treatment was used; only chemical leaching was employed. The reason for the poor removal of heavy metals was that the organic complexing agent could not penetrate the complete glassy encapsulation layer and could only act on the very shallow layer of the particle surface, thus preventing the release of heavy metals from the internal crystal lattice.

[0066] In Comparative Example 2, magnetic separation and ultrasonic treatment were used without the addition of organic complexing agents. Water was used as the medium. Under these conditions, although ultrasonic treatment could physically break the shell, the released heavy metal ions would be rapidly re-adsorbed onto the active sites on the surface of fly ash particles due to electrostatic attraction in the absence of organic complexing agents, or co-precipitate with silicate / aluminate ions in the liquid phase, resulting in an ineffective cycle of desorption-resorption. Therefore, the removal effect of heavy metals was poor.

[0067] In existing technologies, such as CN118527459B, a modified fly ash and its application in saline-alkali soil improvement is disclosed. This method employs graded screening, magnetic separation, and ultrasonic modification. Similar to Comparative Example 2, the heavy metal ions released by ultrasound cannot be treated and instead adsorb onto the surface of fly ash particles or co-precipitate in the liquid phase, resulting in poor removal efficiency. CN110423031A discloses a modification method to improve the strength of fly ash, employing ball milling, soaking, calcination, addition of modifiers, and ultrasonic treatment. Although citric acid is used, its primary purpose is to compound it with water-soluble polyalkylene glycols, sodium pyrophosphate, lauryl alcohol polyoxyethylene ether, fatty alcohol polyoxyethylene ether methylsilane, etc., to improve the dispersibility and stability of fly ash. The ultrasonic step used is for auxiliary dispersion, unlike the present invention which combines organic complexing agents with the ultrasonic step, allowing heavy metals to be captured immediately after release.

[0068] The present invention first removes magnetic components through magnetic separation, avoiding the influence of magnetic components on ultrasound, thereby improving the removal rate of heavy metals during ultrasonic treatment and obtaining non-magnetic fly ash. The removed magnetic components can be utilized according to actual needs.

[0069] When non-magnetic fly ash is mixed with an organic complexing agent solution and subjected to ultrasonic treatment, the glassy coating on the surface of the fly ash particles is broken by ultrasonic cavitation, promoting the release of internal heavy metals. Simultaneously, the low-concentration organic complexing agent promptly captures heavy metal ions, achieving efficient removal of heavy metals such as lead and cadmium. After ultrasonic treatment, filtration is performed to obtain filtrate and filter cake. The solid product (filter cake) obtained from filtration is then washed with a washing liquid. The washing liquid can be returned to the washing process for cleaning the next batch of solid product, or reused as a solvent for preparing fresh citric acid solution, depending on the situation. The waste liquid obtained during the experiment can be discharged in compliance with standards after simple neutralization treatment.

[0070] According to the modification method of this invention, after magnetic separation, when the mass concentration of citric acid is 0.05% to 0.5%, ultrasonication at a frequency of 40 kHz to 80 kHz and a temperature of 40°C to 80°C for 10 to 40 minutes can achieve a considerable removal effect. According to the preparation method of this invention, the removal rate of cadmium (Cd) can reach up to 66.67%, the removal rate of phosphorus (Pb) can reach up to 45.79%, and the removal rate of chromium (Cr) can reach up to 35.86%. The method of this invention can successfully achieve the harmless modification of fly ash and is suitable for pretreatment before resource utilization.

[0071] The above-described embodiments are merely preferred embodiments of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the invention. It should be noted that those skilled in the art can make various improvements and substitutions without departing from the principles of the present invention, and these improvements and substitutions should also be considered within the scope of protection of the present invention. Therefore, the scope of protection of this invention should be determined by the scope of the claims.

Claims

1. A synergistic modification method for removing heavy metals from fly ash, characterized in that, Includes the following steps: The raw fly ash is separated by magnetic separation to remove magnetic components, resulting in non-magnetic fly ash; Non-magnetic fly ash is mixed with an organic complexing agent solution with a mass concentration of 0.05% to 0.5%, and then subjected to ultrasonic treatment at 40℃ to 80℃. During the ultrasonic treatment, heavy metals are released and captured by the organic complexing agent, resulting in modified fly ash.

2. The synergistic modification method for removing heavy metals from fly ash according to claim 1, characterized in that, The ratio of non-magnetic fly ash to organic complexing agent solution is 1g:3mL~8mL.

3. The synergistic modification method for removing heavy metals from fly ash according to claim 2, characterized in that, The mass concentration of the organic complexing agent is 0.1%, and the ratio of non-magnetic fly ash to organic complexing agent solution is 1g:5mL.

4. The synergistic modification method for removing heavy metals from fly ash according to claim 1, characterized in that, During ultrasonic treatment, the ultrasonic frequency is 40kHz to 80kHz and the ultrasonic time is 10min to 40min.

5. The synergistic modification method for removing heavy metals from fly ash according to claim 4, characterized in that, During ultrasonic treatment, the ultrasonic temperature was 60℃, the ultrasonic frequency was 60kHz, and the ultrasonic time was 30min.

6. The synergistic modification method for removing heavy metals from fly ash according to claim 1, characterized in that, The organic complexing agent is one or more of citric acid, oxalic acid, tartaric acid, or ethylenediaminetetraacetic acid.

7. The synergistic modification method for removing heavy metals from fly ash according to claim 1, characterized in that, The magnetic separation method is as follows: magnetic separation at a magnetic intensity of 800kA / m to 1200kA / m for 4 to 45 minutes.

8. The synergistic modification method for removing heavy metals from fly ash according to claim 7, characterized in that, The magnetic separation method is as follows: magnetic separation for 5 minutes at a magnetic separation intensity of 1000 kA / m.

9. Modified fly ash prepared by the synergistic modification method according to any one of claims 1 to 8.

10. The application of the modified fly ash according to claim 9 in the preparation of building material admixtures, saline-alkali land improvement materials, or mine filling materials.

Citation Information

Patent Citations

  • Modification method for improving strength of fly ash

    CN110423031A

  • Preparation method of modified fly ash as well as product and application thereof

    CN118527459A

  • A method for preparing modified fly ash, its products and applications

    CN118527459B